Interview with Yehuda Elkana
Interview with Yehuda Elkana about his first year as the President and Rector of CEU. He talks about the character of the university, the objectives and future goals of the institution. CEU Rector Yehuda Elkana also provides answers to questions related to the Gender and Environmental departments at CEU. Questions are asked by Theresa Agovino.